Evaluating Financial Technology's Global Impact on Banking Efficiency and Customer Satisfaction Across Diverse Regions - Amiruddin, Nabila Putri; Putri, Dhea Aulia; Hasanuddin, Sri Fitriani (Scieclouds Publishing, 2023)
This research aims to first assess FinTech’s effect on the worldwide banking industry, specifically in terms of adoption, efficiency, and customer satisfaction, of key applications. In this context, a quantitative, cross-sectional survey was completed with 478 respondents, comprising banking professional and FinTech users from North America, Europe, Asia, Africa, and Latin America. The study measured the impact of digital payments, online lending, blockchain solutions and robot advisors on customer conversion rates and quantum fund. The study shows that FinTech applications have a positive impact on banking productivity and customer satisfaction levels, especially in the developed countries because of sound legal environment and technologies. Thus, for Africa and Latin America, which have a relatively low level of FinTech development, the following problems are relevant: accessibility and security. These challenges can be effectively captured by t-tests, ANOVA, and multiple regression, the study suggests the requirement for a regional approach to improving the function of FinTech in global banking. Consequently, this study adds more comprehensive and comparative view to the existing literature on the impact of FinTech on the global banking systems and underscores the need for regulatory changes in promoting sustainable FinTech growth. In conclusion, this research makes important contribution to the literature regarding the role of FinTech for improving the inclusiveness and effectiveness of the global financial ecosystem.